1.101. Wyznacz x, jeśli: a) log2 8 + x * logsqrt(3) 3 = log 1 b) (2x – 3) * log4 16 = log2 18 – log2 9 c) log3 1/27 – x * logsqrt(2) 4 = (x + 1) * log 100 d) (x + 2)[log7 3/7 + log3 21] = log4 4 ^ (x – 1) e) log3 3 ^ (2x – 1) – 3 * logsqrt(5) 1/5 = x * log1 8 f) 2x * log5 25 – (3x + 2) * log2 0, 5 = log3 48 – 2 * log3 4 b) log1/3 (81sqrt(3))/(root(4, 3)) log6 (root(3, 36))/216 f) loge c) log1 1/6 + log3 2/3 d) (log5 16 – log5 80) ^ 2 f) logsqrt(2) 50 – logsqrt(2) 25 h) 2 * log1/4 8 – 3 * logsqrt(3) 9 b) 1/2 * log5 4 * log2 30 – log5 6 d) log1 3 * log3 7 * log7 625 8 ^ (log2 5 – 1/3) c) 8 (1/5) ^ (bq, 0, 25 + 1) d) h) 4 ^ (- 1 + log2 3) (4/9) ^ (10g, 5 – 3/2)

1.101. Wyznacz x, jeśli: a) log2 8 + x * logsqrt(3) 3 = log 1 b) (2x – 3) * log4 16 = log2 18 – log2 9 c) log3 1/27 – x * logsqrt(2) 4 = (x + 1) * log 100 d) (x + 2)[log7 3/7 + log3 21] = log4 4 ^ (x – 1) e) log3 3 ^ (2x – 1) – 3 * logsqrt(5) 1/5 = x * log1 8 f) 2x * log5 25 – (3x + 2) * log2 0, 5 = log3 48 – 2 * log3 4 b) log1/3 (81sqrt(3))/(root(4, 3)) log6 (root(3, 36))/216 f) loge c) log1 1/6 + log3 2/3 d) (log5 16 – log5 80) ^ 2 f) logsqrt(2) 50 – logsqrt(2) 25 h) 2 * log1/4 8 – 3 * logsqrt(3) 9 b) 1/2 * log5 4 * log2 30 – log5 6 d) log1 3 * log3 7 * log7 625 8 ^ (log2 5 – 1/3) c) 8 (1/5) ^ (bq, 0, 25 + 1) d) h) 4 ^ (- 1 + log2 3) (4/9) ^ (10g, 5 – 3/2)

Kliknij aby dołączyć do Akademii Matematyki

Dodaj komentarz